Trends in the characteristics of maxillofacial fractures in Nigeria. Journal of Oral and Maxillofacial Surgery - Fasola, A.O; Nyako, E.A; Obiechina, A.E; Arotiba, J.T (My University, 2003)
Purpose The study purpose was to assess the changes in the pattern of maxillofacial fractures in 2 different study periods. Patients and Methods We conducted retrospective study of 341 patients treated for maxillofacial fractures between January 1978 and December 1982 and a prospective study of 483 patients treated between January 1995 and December 1999 at the Department of Oral and Maxillofacial Surgery, University College Hospital, Ibadan, Nigeria. Data were collected on age, gender, etiologic factor, and site of injury. Results The male-to-female ratio reduced in the second period by a factor of 2.0. Patients in the age groups of 21 to 30 years and older than 60 years increased by a factor of 1.8 and 2.9, respectively, in the second period. Assaults, falls, sporting injuries, and industrial accidents in the second period increased by a factor of 1.4, 1.5, 3.5, and 1.5, respectively. The ratio between road traffic accidents and other causes changed from 3.4:1 to 2.2:1 in the second period. Mandibular fractures increased by 2% in the second study period. Conclusion The data confirmed that although other etiologic factors are increasing in number, road traffic accidents remains the major etiologic factor of maxillofacial fractures in Nigeria. There is a need to enforce seat belt use, speed limit, and drink driving laws to reduce maxillofacial injuries caused by road traffic accidents; to organize preventive programs to minimize assaults, and to legislate the wearing of headgear by industrial workers. It has been observed that the incidence and pattern of fractures of the maxillofacial region have changed over the years.1 The most common cause of facial fractures in the world in the past was road traffic accidents,2, 3, 4 and 5 but recent research has revealed that at the present time, the most frequent cause in many nations is assaults.6 Periodic verification of the etiology of maxillofacial fractures helps to assess the proficiency of road safety measures such as speed limit, drunk driving, and seat belt laws and the behavioral patterns of people in different countries and helps to recommend other ways in which injuries to the face can be averted.7 In global literature, studies that examined the changes in pattern of maxillofacial fractures were conducted in Great Britain,8 Germany,9 and The Netherlands,10 but none have been conducted in this region of world. This study, which compares 2 timespans at a Nigerian hospital, was embarked on to review variations in the pattern of maxillofacial fractures and to compare it with similar studies in other regions of the world.